?Seasonal Variations in the Composition of Essential Oil of Eucalyptus citriodora of Pakistan ? (Biological Sciences - PJSIR, 1996)
Gas chromatographi examination of the essential oil. Theoil was examined on a Pye-Unicam 104 gas chromatographunder the following conditions:-